If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -30 + -4(x + 1) = 46 Reorder the terms: -30 + -4(1 + x) = 46 -30 + (1 * -4 + x * -4) = 46 -30 + (-4 + -4x) = 46 Combine like terms: -30 + -4 = -34 -34 + -4x = 46 Solving -34 + -4x = 46 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '34' to each side of the equation. -34 + 34 + -4x = 46 + 34 Combine like terms: -34 + 34 = 0 0 + -4x = 46 + 34 -4x = 46 + 34 Combine like terms: 46 + 34 = 80 -4x = 80 Divide each side by '-4'. x = -20 Simplifying x = -20
| 7(-3+5x)=14 | | 2(2-7)x=-66 | | 6(-2+7x)=240 | | -4(6x+4)=-232 | | (3x-5u+7)(3x+1)= | | 3k+1=7-k | | 2(x*5)-3=0 | | -6(5x+1)=-216 | | 2+11(x+9)=13 | | 4.472135955=20 | | 160-80-4=2y | | Y=.25x+12 | | 4x+4x=7x | | 4(2x-1)=2 | | p=s/s+f | | 2xsquared+9x+7=3 | | 3z-5z^2=30 | | 2/3=(4y-4)/3 | | -9-10x=21 | | x=3x+13 | | 288-16t^2+48t=288 | | 38=4(x+1) | | 4+n=121 | | 2(x+3)-4=2x+2 | | 5x+x=250 | | (12/3-6)= | | 3m-1=5 | | 6x+x=213 | | -200-x=103+2x | | (2w+5)w=403 | | (2x-9/x-7)+x/2=-4/x-7 | | -12*(-3)-(12/3-6)= |